An experimental investigation on the shear and flexural behavior of steel reinforced HPSCC beams - Nikbakht, E. (2019)
High-Performance Self-Compacting Concrete (HPSCC) has experienced increasing demand over the past few years due to its enhanced mechanical properties and high bonding strength. These attributes make it preferable for use in structures, such as tall multi-story buildings, where high workability, strength and bending capacity are required. The objective of the present study is to investigate the shear and flexural behavior of HPSCC beams with no coarse aggregate and compressive strength of above 100 MPa. The influence of different types of steel fibre on the mechanical properties and failure modes of reinforced HPSCC beams were studied. In addition, the influence of the beam's span to effective depth ratio (a/d), longitudinal and transverse reinforcement ratios on the behavior of the HPSCC beams was studied. The results showed that the influence of the type of steel fibre is more significant than the influence of longitudinal reinforcement ratio. Moreover, the ultimate load and deformation capacity of HPSCC beams increased considerably for the beam specimens with steel fibre. However, it was shown that the non-fibre beams with d/4 shear link spacing had a higher ductility compared to the counterpart steel fibre beams with d/2 shear link spacing and with the same amount of longitudinal reinforcement ratio. Â© 2019 Institution of Structural Engineers